The impact of institutional environment factors on foreign direct investment in provinces located in the Mekong delta region - Nguyen, Ba Hoang; Vu, Thanh An; Le, Hoang Phong (The Economics and Finance Letters, 2024)
The primary aim of this study is to explore the influence of institutional environmental factors on foreign direct investment (FDI) within the provinces of Vietnam’s Mekong Delta region over the period from 2010 to 2022. The fixed-effect model (FEM) and random-effect model (REM) are used for estimating the impacts of the institutional environment’s elements on the FDI of Vietnam’s provinces. The Hausman’s test is applied to help determine a suitable and reliable model to perform analyses and discuss the empirical results. The research results indicate that institutional environment factors have a significant impact on FDI inflows in the provinces. Specifically, enterprise support and the number of FDI projects foster the FDI inflows in the provinces of Mekong Delta region. Furthermore, factors such as cost of market entry, information transparency, informal costs, the dynamics of the leaders at the provincial level, the level of labor training, and legal institutions do not significantly influence the FDI inflows into the provinces. Based on these findings, the main policy implications, including improving enterprise support and increasing the number of FDI projects to attract more FDI inflows to the provinces in the Mekong Delta region of Vietnam, have also been proposed.